Qualitative exploration of the needs of pregnant women to manage the fear of childbirth - Azam Bakhteh; Nasrin Jaberghaderi; Mastaneh Kamravamanesh; Mitra Kolivand; Mansour Rezaei; Zahra Motaghi (Wolters Kluwer Medknow Publications, 2023)
Background: Some women experience the Fear of Childbirth (FOC) during pregnancy, labor, and birth which can have consequences for their health and well-being. To provide the right conditions for having a positive experience of childbirth, the needs of pregnant women must be correctly recognized. The present study was conducted with the aim of investigating the needs of women in managing the FOC with a qualitative design. Materials and Methods: This qualitative study was conducted using conventional content analysis from January to November 2021. To this aim, 15 pregnant women, 21 healthcare providers, and four maternal health policymakers were purposefully selected from Kermanshah health centers, with maximum diversity. Data were collected through in-depth semi-structured interviews. Data accuracy was guaranteed using Lincoln and Guba criteria. The MAXQDA software was used for data analysis. Results: From the analysis of the data obtained from the interviews, three main categories emerged concerning the needs of mothers to properly manage the FOC: "need to provide awareness and empowerment of mother and family," and "the need to pay attention to the mental health of pregnant women," and "supporting needs (seeking support)." Conclusions: Identifying and paying attention to woman's needs in the areas of education, mental health, and support can help them manage crisis-ridden situations, including the FOC. In response to the needs of mothers to empower them in managing the FOC, it is recommended to formulate special guidelines in this field.